2019
DOI: 10.1002/cyto.b.21862
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations for the high sensitivity detection of multiple myeloma measurable residual disease

Abstract: Background Recent advances in therapeutic interventions have dramatically improved complete response rates in patients with multiple myeloma (MM). The ability to identify residual myeloma cells (e.g., measurable residual disease [MRD]) can provide valuable information pertaining to patient's depth of response to therapy and risk of relapse. Multiparametric flow cytometry is an excellent technique to monitor MRD and has been demonstrated to correlate with patient outcome post‐treatment. To achieve the high sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Although adopting this approach results in the acquisition of more than 10 7 cells per sample, the method may not be feasible for widespread adoption due to time, labor, and cost requirements (EuroFlow, 2018;Flores-Montero, Sanoja-Flores, Paiva, et al, 2017;Kalina, Flores-Montero, van der Velden, et al, 2012). Alternatively, although pooling the analysis of multiple aliquots of unconcentrated bone marrow processed by post-lysis achieves a similar high sensitivity, this results in extra reagent cost and acquisition time (Soh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although adopting this approach results in the acquisition of more than 10 7 cells per sample, the method may not be feasible for widespread adoption due to time, labor, and cost requirements (EuroFlow, 2018;Flores-Montero, Sanoja-Flores, Paiva, et al, 2017;Kalina, Flores-Montero, van der Velden, et al, 2012). Alternatively, although pooling the analysis of multiple aliquots of unconcentrated bone marrow processed by post-lysis achieves a similar high sensitivity, this results in extra reagent cost and acquisition time (Soh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have directly compared assay performance of pre-lysis against post-lysis (Kalina et al, 2012;Muccio, Saraci, Gilestro et al, 2018;Royston et al, 2016;Soh et al, 2020). In this article, we report on the evaluation of our department's standard postlysis preparation (SLW) against a modified EuroFlow pre-lysis (LSW) method to evaluate overall assay sensitivity in assessment of MRD using routine samples from patients with hematological malignancies for which MFC MRD plays an important clinical role.…”
Section: Introductionmentioning
confidence: 99%
“…This current study underscores techniques and methodologies found in recent Another Abundance of Riches and more Issue Highlights!! publications in this journal assessing the presence of lymphoid and plasma cell malignancies (Cherian et al, 2019;DiGiuseppe et al,2019;Jevremovic et al, 2019;Seegmiller et al, 2019;Soh et al, 2020).…”
mentioning
confidence: 99%
“…This has been driven in part by the long‐lasting remissions many patients on clinical trials achieve and the need for surrogate endpoints of progression free survival to speedily evaluate novel therapeutics (1‐3). To achieve the sensitivities of 10 ‐5 ‐ 10 ‐6 required for MRD assessment, more cells than can normally be obtained from 100 μL of blood or bone marrow are required (4). Laboratories have developed several methods to obtain the 5‐10 x 10 6 cells per tube required for MRD assays but a standardized approach is needed (5).…”
mentioning
confidence: 99%